دراسة موسمية لبعض الخصائص الفيزيائية والكيميائية لمياه ورواسب نهر الغراف - عبد الرضا علي, ساهر; عريبي حسين, محسن; تركي خثي, محمد (University of Thi-Qar Journal of Science, 2009)
The physical and chemical parameters of water and sediments for Garaf river during four seasons from summer 2007 until spring 2008 were studied in ten locations alongside the river starting from The Kut Dam when the river branching from the Tigris to its end in the northern of Nassiria city .The stations were chosen according to population density and pollution probability. The investigated parameters include temperature, pH, conductivity, total alkalinity, calcium, magnesium, chloride, phosphate, nitrate ,sulfate, sodium, potassium and lithium for water and sediment . Water temperature ranged between(17 - 34) C0(18 -37) Cowhich in accordance with air . pH values for the ten locations throughout the year period of study located between (6.9 -8.3),also the sediments recorded low alkalinity, ranged between 7.4- 8.4 .The highest conductivity for water recorded 1292 µS/cm but the lowest was 928 µS/cm. While the sediments showed a high rate of conductivity 1793 µs/cm and the lowest was 1221 µS/cm. The high total alkalinity for water recorded 373 mg/l but the lowest was114 mg/l. while the sediments showed a high rate of total alkalinity270mg/l the lowest value123mg/l.The total chloride, calcium, magnesium, sulfate, phosphate ,nitrate, sodium, potassium, and lithium for water ranged between( 265-123) mg/l (112-64)mg/l (93-19)mg/l (167-123)mg/l (0.8-0.1)mg/l (7.5-1.9)mg/l (123-24)mg/l (97-12)mg/l (0.8-0.1) mg/l respectively while for sediment they ranged between(265-140) mg/l (144-65)mg/l (68-23 )mg/l (278 -57)mg/l (5.3-1.2)mg/l (20-10.2)mg/l (117-58)mg/l (77-24)mg/l (2.2-0.1) mg/l respectively .